Developmental trajectories of loneliness and social support in older adults: based on the parallel process latent growth curve model - Chang Hu; Yuhan Chen; Xin Li; Xi Wang; Jin Chu (Frontiers in Public Health)
BackgroundWith the acceleration of global aging, loneliness among older adults has become a prominent issue and a critical public health concern. Existing research has primarily focused on the cross-sectional relationship between social support and loneliness, but longitudinal dynamics and bidirectional mechanisms remain underexplored. This study aims to explore the developmental trajectories and interaction between loneliness and social support among Chinese older residents in the community.MethodsThe study was conducted with three waves of data collection (6-month intervals) over 1 years, involving 1,225 Chinese older residents in the community. The Navigating the Social Support Scale and the UCLA Loneliness Scale were used to measure social support and loneliness, respectively. Cross-lagged panel modeling (CLPM) was employed to examine bidirectional predictive relationships, while parallel process latent growth curve modeling (LGCM) was applied to assess associations between initial levels and developmental rates of the two constructs.Results(1) The loneliness of the older adults gradually increased over time, while the level of social support slowly decreased. (2) Loneliness could negatively predict social support from T1 to T2, and T2 to T3, but only social support at T1 negatively predicted loneliness at T2. (3) The initial level of loneliness could negatively predict the development speed of social support, and social support could also negatively predict the development speed of loneliness.ConclusionWe found that that high loneliness is a risk factor in the development of social support levels, and high social support is also a protective factor in the development of loneliness, which provides empirical evidence for the study of emotional health in the older adults.